Young People Speak Out : Youth Consultations for the World Development Report 2007 - Mangiaterra, Viviana; Vollmer, Gerold (World Bank, Washington, DC, 2018)
The following pages relate to the experience of over three thousand young people with regards to what it means for them to be coming of age in today’s world. Between September 2005 and April 2006, these young women and men met in twenty-six developing countries to talk about what concerns them: getting a degree, landing a job, staying healthy, finding a partner, moving into their own place, and making a difference in their society. By voicing their concerns and policy demands, these young people contributed to what is universally regarded as one of the most influential perennial development research publications: The World Development Report (WDR). The authors of the report recognized the value of listening to the subjects of their research and working together with a team of consultation experts to devise what may well be among the most extensive stakeholder consultation processes to date. Given the focus of the 2007 WDR on youth, it was especially important to devise a consultative process that will foster a dialogue not only about youth but also with young people themselves. At the same time, it had to be made clear to the youth constituency that the report could not be written by youth. The consultations had three clearly stated objectives: information, validation, and traction. They provided information to the team of researchers to learn about and understand the perspectives of the young people. Moreover, the dialogue with the youth in developing countries helped the team to validate their research. Finally, the consultations were also a key instrument to foster political traction with global youth organizations, governmental agencies, and development partners to enhance the ‘operationalization’ of the report.